Role of transmembrane segment 5 of the plant vacuolar H+-pyrophosphatase - Van, R.C.; Pan, Y.J.; Hsu, S.H.; Huang, S.T.; Hsiao, Y.Y.; Pan, R.L.
Vacuolar H+-translocating inorganic pyrophosphatase (V-PPase; EC 3.6.1.1)is a homodimeric proton translocase consisting of a single type of polypeptide with a molecular mass of approximately 81 kDa. Topological analysis tentatively predicts that mung bean V-PPase contains 14 transmembrane domains. Alignment analysis of V-PPase demonstrated that the transmembrane domain 5 (TM5)of the enzyme is highly conserved in plants and located at the N-terminal side of the putative substrate-binding loop. The hydropathic analysis of V-PPase showed a relatively lower degree of hydrophobicity in the TM5 region as compared to other domains. Accordingly, it appears that TM5 is probably involved in the proton translocation of V-PPase. In this study, we used site-directed mutagenesis to examine the functional role of amino acid residues in TM5 of V-PPase. A series of mutants singly replaced by alanine residues along TM5 were constructed and over-expressed in Saccharomyces cerevisiae; they were then used to determine their enzymatic activities and proton translocations. Our results indicate that several mutants displayed minor variations in enzymatic properties, while others including those mutated at E225, a GYG motif (residues from 229 to 231), A238, and R242, showed a serious decline in enzymatic activity, proton translocation, and coupling efficiency of V-PPase. Moreover, the mutation at Y230 relieved several cation effects on the V-PPase. The GYG motif presumably plays a significant role in maintaining structure and function of V-PPase.
Keywords: PROTON TRANSLOCATION; TONOPLAST; VACUOLE; VACUOLAR H+-PYROPHOSPHATASE; SITE-DIRECTED MUTAGENESIS; GYG MOTIF